2014
DOI: 10.4037/ajcc2014362
|View full text |Cite
|
Sign up to set email alerts
|

Infection Rates in Intensive Care Units by Electrocardiographic Lead Wire Type: Disposable vs Reusable

Abstract: A closed-book, multiple-choice examination following this article tests your under standing of the following objectives: Patients' characteristics and infections were collected from hospital databases. Event rates were described by using total counts and rates per 100 patient days and were compared between groups by using generalized linear mixedeffect models weighted by patients' ICU length of stay. Results Overall, 4056 patients from 6 ICUs received disposable and 3184 patients from 5 ICUs received reusable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“… 21 Lower contamination rates are seen with spECG. 14 , 15 A United States (US) analysis of 27,000 CABG procedures found a 25% reduction in SSI following CABG in hospitals implementing spECG. 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Lower contamination rates are seen with spECG. 14 , 15 A United States (US) analysis of 27,000 CABG procedures found a 25% reduction in SSI following CABG in hospitals implementing spECG. 16 …”
Section: Introductionmentioning
confidence: 99%
“…12 Reports indicate that circa 3.6% of Australian CABG patients develop SWIs. 13 Several care improvement initiatives have been successful in reducing the rate of SWIs, [14][15][16] showing that the introduction of new medical technologies has the potential to eliminate a subset of avoidable infections. Key changes which have proven effective include the introduction of impregnated sutures, new wound dressings, and single-patient-use electrocardiograph (spECG) cable and lead systems.…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized that single-patient ECG leads and wires (spECG) would reduce the incidence of SSI by limiting the possibility of cross-contamination. Albert et al compared rECG and spECG, finding no difference in infections (not just SSI) acquired in the ICU, though noting that implementation of additional infection control measures drastically reduced HAI rates during the course of the study (15, 16). More recently, a Medicare claims analysis observing over 27,000 CABG surgeries found that facilities using spECG (Kendall™ DL, Cardinal Health, Dublin, OH) had a 25% reduction ( p > 0.05) in SSIs at 90 days post procedure (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the absence of clinical outcomes, this advice should be interpreted with caution. In a large randomized controlled trial encompassing more than 7200 patients, Albert and colleagues 85 could not demonstrate a difference in infection rate between ICU patients with disposable and reusable ECG lead wires.…”
Section: Infection Prevention and Controlmentioning
confidence: 99%